The emancipation of disability studies in Portugal - Fontes, Fernando (2014)
Despite the interest of the social sciences in issues of exclusion and inequality, the question of disability, as a key issue of reflection, remains absent from many academic areas. The emergence of disability studies owes much to contexts in which the activism of disabled people has revealed the structural conditions that oppress and neglect experiences of disability. Bearing in mind the specific features of the Portuguese socio-political environment, two lines of inquiry are developed in this text. Firstly, what are the challenges faced by Portuguese academics in making disability a central issue, enabling it to confront the silencing of the voices and experiences of disabled people in society? Secondly, how important is it for research to engage with an ethical and political paradigm that supports the rights of disabled people?